A Novel Amperometric Glutamate Biosensor Based on Glutamate Oxidase Adsorbed on Silicalite - O. V. Soldatkina; O. O. Soldatkin; B. Ozansoy Kasap; D. Yu. Kucherenko; I. S. Kucherenko; B. Akata Kurc; S. V. Dzyadevych (Nanoscale Research Letters, 2017)
Abstract In this work, we developed a new amperometric biosensor for glutamate detection using a typical method of glutamate oxidase (GlOx) immobilization via adsorption on silicalite particles. The disc platinum electrode (d = 0.4 mm) was used as the amperometric sensor. The procedure of biosensor preparation was optimized. The main parameters of modifying amperometric transducers with a silicalite layer were determined along with the procedure of GlOx adsorption on this layer. The biosensors based on GlOx adsorbed on silicalite demonstrated high sensitivity to glutamate. The linear range of detection was from 2.5 to 450 μM, and the limit of glutamate detection was 1 μM. It was shown that the proposed biosensors were characterized by good response reproducibility during hours of continuous work and operational stability for several days. The developed biosensors could be applied for determination of glutamate in real samples.